2021
DOI: 10.3126/mjmms.v1i1.42945
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Pay and Expected Benefits for Social Health Insurance: A Cross-sectional Study at Pokhara Metropolitan City

Abstract: INTRODUCTION: The government supported SHI is the largest health insurance schemes ever launched in the country since 2016 by Health Insurance Board. Prior to UHI program, small scale community health insurance programs are running in fragmented structure The paper aims to examine the association between the potential policyholder's paying willingness for the social health insurance their characteristics, and tries to predict the willingness to pay for social health insurance schemes and their expected benefit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…In research carried out in various countries, socioeconomic characteristics were reported to affect people's WTP for health insurance programs. Accordingly, the WTP for SHI was found to be influenced by age ( 41 , 44 , 47 ), gender ( 40 , 42 , 44 , 48 ), level of education ( 40 , 42 , 44 , 47 , 49 52 ), residence ( 40 , 41 ), household size ( 40 , 44 , 47 49 , 52 ), occupational status ( 40 , 49 ), household income ( 40 , 47 , 49 , 51 ), and marital status ( 50 ). Thus, it might be important to consider the socio-demographic diversity of the population in the formal sector while implementing SHI.…”
Section: Discussionmentioning
confidence: 99%
“…In research carried out in various countries, socioeconomic characteristics were reported to affect people's WTP for health insurance programs. Accordingly, the WTP for SHI was found to be influenced by age ( 41 , 44 , 47 ), gender ( 40 , 42 , 44 , 48 ), level of education ( 40 , 42 , 44 , 47 , 49 52 ), residence ( 40 , 41 ), household size ( 40 , 44 , 47 49 , 52 ), occupational status ( 40 , 49 ), household income ( 40 , 47 , 49 , 51 ), and marital status ( 50 ). Thus, it might be important to consider the socio-demographic diversity of the population in the formal sector while implementing SHI.…”
Section: Discussionmentioning
confidence: 99%
“…The drop in WTP for SHI with age may be attributed to the fact that as people get older, their supplemental income sources decrease, making them unable to afford the premium. However, it has also been discovered that older people are willing to pay a higher premium than younger people ( 46 ).…”
Section: Discussionmentioning
confidence: 99%